A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1984)
This article reviews the book, "A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914", edited by Susan Jackel.